Pengaruh Social Media Marketing dan Kualitas Produk Terhadap Keputusan Pembelian pada UMKM Fashion Traguardo - Rido Ihsan; Ramadhan Rafael Azzra; Erna Herlinawati (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the influence of Social Media Marketing and Product Quality on Purchase Decisions at Traguardo Fashion MSME. The study was motivated by the company's inability to achieve its sales targets despite utilizing social media as a digital marketing platform and maintaining product quality. This research employed a quantitative method with descriptive and verificative approaches. The population consisted of Traguardo Fashion consumers, with a sample of 104 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results indicate that Social Media Marketing has a positive and significant effect on Purchase Decisions, with a t-value of 7.261 and a significance level of 0.000. Product Quality also has a positive and significant effect on Purchase Decisions, with a t-value of 6.102 and a significance level of 0.000. Simultaneously, Social Media Marketing and Product Quality significantly affect Purchase Decisions, as indicated by an F-value of 62.333 and a significance level of 0.000. The Adjusted R Square value of 0.544 indicates that 54.4% of the variation in Purchase Decisions can be explained by the independent variables, while the remaining 45.6% is influenced by other factors outside the research model. The findings reveal that Social Media Marketing is the most dominant factor influencing consumer Purchase Decisions. Therefore, Traguardo Fashion MSME should optimize its social media marketing activities and consistently maintain product quality to enhance consumer purchase decisions